2022
DOI: 10.1177/10499091221129602
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets (and Who Should Get) a Serious Illness Conversation in the Hospital? An Analysis of Readmission Risk Score in an Electronic Health Record

Abstract: Serious Illness Conversations (SICs) explore patients’ prognostic awareness, hopes, and worries, and can help establish priorities for their care during and after hospitalization. While identifying patients who benefit from an SIC remains a challenge, this task may be facilitated by use of validated prediction scores available in most commercial electronic health records (EHRs), such as Epic’s Readmission Risk Score (RRS). We identified the RRS on admission for all hospital encounters from October 2018 to Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Baseline characteristics ( Table 1 ) demonstrated that prior to matching, encounters with standardized documentation of a SIC were more frequently older, more frequently female, less frequently Hispanic, and more frequently insured by Medicare. Encounters with standardized documentation of a SIC also had higher Elixhauser/Van Walraven comorbidity scores, 29 RRS, 28 and eCART 27 scores and more likely to have had a hospitalization in the year prior to index hospitalization. Following propensity score matching, variables used in matching were balanced between groups, with SMDs of < ±.1 except for DRG weight, which had an SMD of .21.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Baseline characteristics ( Table 1 ) demonstrated that prior to matching, encounters with standardized documentation of a SIC were more frequently older, more frequently female, less frequently Hispanic, and more frequently insured by Medicare. Encounters with standardized documentation of a SIC also had higher Elixhauser/Van Walraven comorbidity scores, 29 RRS, 28 and eCART 27 scores and more likely to have had a hospitalization in the year prior to index hospitalization. Following propensity score matching, variables used in matching were balanced between groups, with SMDs of < ±.1 except for DRG weight, which had an SMD of .21.…”
Section: Resultsmentioning
confidence: 98%
“…Though inpatient palliative care consultation is typically reserved for patients with the highest mortality risk, 30,31 our ability to successfully propensity match in a ratio of 1: 3 suggests that other high-risk patients may have unmet palliative care and end-of-life needs that were not formally elicited and addressed during the hospital encounter. A variety of barriers to conducting SICs and to using the structured EHR module to document the conversation during the hospital encounter may explain this gap, including limited availability of palliative care consultants, 32 lack of standardized indications for palliative care consultation, 33 difficulty with prognostication, 28,34 limited clinician time, suboptimal training or discomfort with leading these conversations and documenting them in the institutionally-approved manner. 1 Achieving a healthcare system that values and prioritizes patient-centeredness requires that hospital-based clinicians have tools, training and resources to identify patients with elevated mortality risk, conduct these conversations and document these conversations so they can readily be carried forward in the medical record.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dillon et al 2020 [149], Nolan et al 2020 [150] Adolescent Austrian et al [151], 2018; Brooks et al [152], 2016; Carter et al [153], 2017; Chiu et al [154], 2018; Clendennen et al [155], 2015; Dowling et al [156], 2018; Flatow et al [157], 2015; Isseh et al [158], Adult 2017; Javier-DesLoges et al [159], 2018; King et al [160], 2020; Loo and Taddei [161], 2015; Makam et al [162], 2013; Mathias et al [163], 2010; McDowell et al [164], 2017; Muqri et al [165], 2022; Nikolian et al [166], 2018; Osband et al [167], 2018; Rizk et al [168], 2020; Rodriguez et al [169], 2021; Salem et al [170], 2023; Serna et al [171], 2022; Su et al [172], 2018; Vlashyn et al [173], 2023; Wagner et al [174], 2015; Zazove et al [175], 2017 Altice and Gerow [176], 2020; Bellon et al [177], 2015; Burns et al [178], 2022; Everson et al [179], 2016; Handley et al [180], 2022; Nellis et al [181], 2022; Sahu et al [182], 2022; Simon et al [183], 2023 Adult and pediatric Palestine et al [184], 2018 Not applicable Bush et al [185], 2014; Bush et al [186], 2017; Havrilla et al [187], 2022; Redd et al [188], 2014 Pediatric Beiser et al…”
Section: Health Services Researchmentioning
confidence: 99%